ANALISIS KEPUASAN KERJA GURU MADRASAH TSANAWIYAH NEGERI 2 BALIKPAPAN - Tanjung, Ronaaziyyah; Hasan, Syahril; Yulianti, Tutik (Jurnal GeoEkonomi, 2025)
The purpose of this study was to determine the effect of Work Motivativon, Work Environment and Communication on Job Satisfaction of teachers at the Madrasah Tsanawiyah Negeri 2 Balikpapan. The sampling technique in this study was purposive sampling with a sample 34 teachers from the Madrasah Tsanawiyah Negeri 2 Balikpapan. Methods of data collection is done by distributing questionnaires. This study uses SmartPLS in processing data. The results of this study indicate that the motivation variable has a significant effect on job stratification of teachers at the Madrasah 2 Negeri Balikpapan. Work Environment variable has no significant effect on job stratification of employees at the Madrasah Tsanawiyah Negeri 2 Balikpapan. Communication variable has a significant effect on job stratification of teachers at the Madrasah Negeri 2 Balikpapan.